2017
DOI: 10.1016/j.gaceta.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender effects on the prevalence of poor sleep quality in the adult population

Abstract: The prevalence of poor sleep quality is high among adults, especially women. There is a direct relationship between age and deterioration in the quality of sleep. This relationship also appears to be more consistent in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
164
7
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(226 citation statements)
references
References 26 publications
38
164
7
17
Order By: Relevance
“…In the present study, we found that female gender was associated with an increased likelihood of poor sleep quality, which is in line with the current view that women are more prone than men to experiencing sleep disorders [32][33][34]. The epidemiologic studies have indeed frequently indicated that female gender is an independent risk factor for sleep disorders [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that female gender was associated with an increased likelihood of poor sleep quality, which is in line with the current view that women are more prone than men to experiencing sleep disorders [32][33][34]. The epidemiologic studies have indeed frequently indicated that female gender is an independent risk factor for sleep disorders [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…These are higher scores than reported in general population and non-clinical samples [5759], suggesting more and worse sleep problems, as might be expected in this group. These scores should suggest a sample ranging from those with multiple and severe problems, to good sleepers, although it is noted that those obtaining relatively low scores often described severe problems in interview.…”
Section: Resultscontrasting
confidence: 38%
“…Problems with sleep may severely impact our cognitive functioning (Alhola and Polo-Kantola, 2007) and health (Garbarino et al, 2016;Kecklund and Axelsson, 2016). More than one third of the adult population suffers from insufficient sleep or impaired sleep quality (Liu, 2016;Madrid-Valero et al, 2017), with significant consequences for our economy (Hafner et al, 2017). Current therapies for sleep problems include pharmacological (Wilson and Nutt, 2010) and psychological or behavioral therapies, including relaxation strategies (Edinger et al, 2017;Morin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%